2008
DOI: 10.1097/mcg.0b013e318046eac3
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori Infection and Development of Gastric Cancer in Korea

Abstract: The present study shows a close relationship between H. pylori infection and IM, and between IM and the development of gastric cancer. In addition, our finding suggests that chronic H. pylori infection looks like an important risk factor for the development of gastric cancer in Korea, where the prevalence of H. pylori remains high. This study indicates that to prevent gastric cancer H. pylori eradication is best performed before the development of IM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(84 citation statements)
references
References 22 publications
2
76
0
3
Order By: Relevance
“…In present study, we directly compared the occurrence of GC and the results suggested that patients with IM or DYS may not benefit from the H. pylori treatment on the risk of GC. Similar results indicating that the baseline of IM was a prior risk factor of GC development after eradication can be obtained in other studies [22][23][24].In the aspect of primary-prevention, Mera et al [8] prescribed eradication therapy to participants allocated in placebo group and prolong the follow up duration from 6 to 12 years, and all 9 GC patients had a baseline diagnosis of IM or DYS. A large population-based study with 4,121 participants showed the 5-year average incidence of GC decreased from 40.3 to 30.4 per 100 000 person-yearsafter eradication treatment.…”
Section: Discussionsupporting
confidence: 69%
“…In present study, we directly compared the occurrence of GC and the results suggested that patients with IM or DYS may not benefit from the H. pylori treatment on the risk of GC. Similar results indicating that the baseline of IM was a prior risk factor of GC development after eradication can be obtained in other studies [22][23][24].In the aspect of primary-prevention, Mera et al [8] prescribed eradication therapy to participants allocated in placebo group and prolong the follow up duration from 6 to 12 years, and all 9 GC patients had a baseline diagnosis of IM or DYS. A large population-based study with 4,121 participants showed the 5-year average incidence of GC decreased from 40.3 to 30.4 per 100 000 person-yearsafter eradication treatment.…”
Section: Discussionsupporting
confidence: 69%
“…Another systematic review also concluded that there is sufficient clinical evidence that H. pylori eradication has a role in the prevention of gastric cancer in patients with chronic non-atrophic gastritis and with atrophic gastritis [226]. Indeed, a large prospective study (mean follow-up of 9.4 years) also suggested that H. pylori eradication before the development of intestinal metaplasia is probably more effective in reducing gastric cancer incidence [235].…”
Section: Surveillancementioning
confidence: 96%
“…The patients with H. pylori infection and IM had more than 6.4-fold increased risk of gastric cancer than the subjects of infected with H. pylori infection but without IM [ 3 ]. In a cohort study of 2,224 subjects conducted in South Korea, the group with IM had 10.9-fold increased risk of gastric cancer [ 19 ]. H. pylori infection triggers a multistep progression from chronic gastritis, gastric atrophy, IM, and fi nally into gastric cancer [ 29 ].…”
Section: Atrophic Gastritis and Intestinal Metaplasia As Precursor Lementioning
confidence: 94%